Implementasi Pendekatan PMRI pada Materi Peluang di SMP untuk Meningkatkan Kemampuan Numerasi Siswa - Inayatusufi, Chairunnisa; Makmuri, Makmuri; Meiliasari, Meiliasari (PAKAR Pendidikan, 2024)
Students with good numeracy skills will help them in solving problems. However, based on the PISA results, in reality educational results in this domain are still below standard, one of which is in the concept of opportunity which is one of the numeracy content domains. Based on this, the aim of this research is to determine the application of Indonesian Realistic Mathematics Education learning in improving students' numerical abilities in class VIII opportunity concepts. This PTK research was carried out in three cycles consisting of planning, implementation, observation, analysis and reflection. The research subjects (SP) were 6 class VIII students at Al-Chalidyah Middle School. This research applies the PMRI stages. At each meeting, students are given worksheets as a learning tool that contains numeracy problem solving as a form of phenomenological exploration, use models, student contribution, interactivity, and intertwinment, so that students can find the concepts being studied that are adapted to indicators of numeracy ability. The results of the research stated that students' ability to understand mathematical concepts had increased. This can be seen from the students' process of participating in learning activities and also the increase in the average score of the SP cycle tests. The results for cycle I were 65.97, cycle II 75.00 and cycle III 82.10. So it can be concluded that PMRI learning can improve numeracy skills on occasion.